A força normativa da súmula vinculante no processo decisório do juiz - Lacerda, Allan Dias (2011)
This dissertation deals with the attitude of the magistrate before the binding judicial precedent1 , showing how the magistrate must act before a possible contradiction between the binding judicial precedent and other normative acts. To do this, makesis an analysis of the legal rule, studying its meaning, and their conditions of existence, validity, in force and effectiveness. Investigates the concept of legal system, its unity and its hierarchical structure, which requires a consistency of its elements to get working properly. Also addresses the issue involving the Supreme Court, stating that it should be seen as a Constitutional Court in contemporary society. It shall, moreover, the concept of binding judicial precedent and its legal status, saying that it is an interpretive rule of law and discussing its history, beyond its main objectives, among which may be cited as legal certainty and speedy trial. Analyzes the provision dealing the binding judicial precedent laid down in Article 103-A of the Constitution and the law 11471/2007, especially those that set their requirements and their scope. It argues that the magistrate keeps intact his hermeneutic powers before the binding judicial precedent. In the end, deals with the conflict between the binding judicial precedent and other rules in the system, saying what should be the attitude of judges in each situation.